Targeting microbial pathogenic mechanisms as a novel therapeutic strategy in IBD - Paul F. Miller (BMC, 2024)
Abstract Background Current therapy for patients suffering from inflammatory bowel diseases (IBD) is focused on inflammatory mechanisms exclusively and not the dysbiotic microbiota, despite growing evidence implicating a role for intestinal microbes in disease. Main body Ongoing research into the intestinal microbiota of IBD patients, using new technologies and/or deeper application of existing ones, has identified a number of microorganisms whose properties and behaviors warrant consideration as causative factors in disease. Such studies have implicated both bacteria and fungi in the pathogenesis of disease. Some of these organisms manifest mechanisms that should be amenable to therapeutic intervention via either conventional or novel drug discovery platforms. Of particular note is a deeper characterization of microbial derived proteases and their destructive potential. Conclusion Given the steady progress on the mechanistic role of the microbiota in inflammatory diseases, it is reasonable to anticipate a future in which therapeutics targeting microbial derived pathogenic factors play an important role in improving the lives of IBD patients.